A Study the History and Evolution of Social Networking and Social Media with its benefits: Exploring the Impact and Influence of Social Networking and Social Media (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The term Social Media refers to a collection of software websites that give users a place topost, share, and connect with one another. This interactive computer-mediated technology provides a meansfor people to communicate with each other in a variety of ways beyond simply changing their status oruploading photographs to social media. For social transformation, social media is a powerful weapon in thearsenal. It is frequently employed to promote public awareness of critical topics. Here, we'll take a look atsome of the most popular social networking sites of the 21st century.